Herbal treatment with uva ursi extract versus fosfomycin in women with uncomplicated urinary tract infection in primary care: a randomized controlled trial. (October 2021) - Gágyor, Ildikó; Hummers, Eva; Schmiemann, Guido; Friede, Tim; Pfeiffer, Sebastian; Afshar, Kambiz; Bleidorn, Jutta
Abstract: Objective: We explored whether initial treatment with the herbal drug uva ursi (UU) reduces antibiotic use in women with uncomplicated urinary tract infection (UTI) without increasing symptom burden and complication frequency compared with antibiotic treatment. Methods: A double-blind randomized controlled trial was conducted in 42 family practices in Germany. The participants were adult women with suspected uncomplicated UTIs receiving either UU 105 mg 3 × 2 tablets for 5 days (intervention) or fosfomycin a 3-g single dose (control), and their respective placebos. Participants and investigators were blinded. The primary outcome included (1) antibiotic courses day 0–28 as superiority, and (2) symptom burden (sum of daily symptom scores) day 0–7, as non-inferiority outcome (margin 125%). Clinicaltrials.gov: NCT03151603 . Results: Overall, 398 patients were randomly allocated to groups receiving UU ( n = 207) and fosfomycin ( n = 191). The number of antibiotic courses was 63.6% lower (95% CI 53.6%–71.4%; p < 0.0001) in the UU group than in the fosfomycin group. The ratio of total symptom burden in the UU group compared with control was 136.5% (95% CI 122.7–151.9; p 0.95), failing non-inferiority. Eight women developed pyelonephritis in the UU group compared with two in the fosfomycin group (mean difference 2.8; 95% CI 0.2–5.9; p 0.067). Adverse events were similar between the groups. Discussion: In women with uncomplicated UTIs, initial treatment with UU reduced antibiotic use but led to a higher symptom burden and more safety concerns than fosfomycin.